3 300 V IGBT Based on Enhanced Trench Metal Oxide Semiconductor Technology with High Performance - ZHOU Feiyu; NING Xubin; Luther Ngwendson; XIAO Qiang; Ian Deviny; DAI Xiaoping (Kongzhi Yu Xinxi Jishu)
It developed a new enhanced trench metal oxide semiconductor (TMOS+) 3 300 V IGBT with soft punch through (SPT) concept and n-well layer. Its on-state voltage (Tj=150 ℃ ) is 25% lower than that of 3 300 V planar enhanced double diffused metal oxide semiconductor (DMOS+) IGBT, and its reverse bias safe operation area (RBSOA) is robust with 11 times rated current turn-off capability. Hence, the rated current of the TMOS+ IGBT module is 20% increased than the conventional one with the same size, which has more benefit for higher power applications.